2000
DOI: 10.1063/1.372290
|View full text |Cite
|
Sign up to set email alerts
|

Analytic model of direct tunnel current through ultrathin gate oxides

Abstract: A theoretical model for tunnel leakage current through 1.65–3.90-nm-thick gate oxides in metal-oxide-semiconductor structures has been developed. The electron effective mass in the oxide layer and the Fermi energy in the n+ poly-Si gate are the only two fitting parameters. It is shown that the calculated tunnel current is well fitted to the measured one over the entire oxide thickness range when the nonparabolic E-k dispersion relationship for the oxide band gap is employed. The electron effective mass in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 29 publications
7
55
0
2
Order By: Relevance
“…Nevertheless, some studies had shown a contradicting effect: If the effective mass is supposed to be 0.5m e , then barrier height is obtained around 2.9-3.1 eV, 30,31 whereas if barrier height is taken to be as 3.1 eV then effective mass was found as 0.37m e . 32 Khairurrijal et al 33 showed from their theoretical calculations that the effective mass of electrons in SiO 2 oxide film increases when the oxide thickness gets decreased, having a value between 0.3m e and 0.9m e . Upon assuming constant electron effective mass at 0.5m e in oxide film, Hadjadj et al 22 added the effect of oxide thickness on electron affinity difference for 5, 7, and 12 nm thick oxides for the temperature ranging from 23 to 300°C.…”
Section: ͑8͒mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some studies had shown a contradicting effect: If the effective mass is supposed to be 0.5m e , then barrier height is obtained around 2.9-3.1 eV, 30,31 whereas if barrier height is taken to be as 3.1 eV then effective mass was found as 0.37m e . 32 Khairurrijal et al 33 showed from their theoretical calculations that the effective mass of electrons in SiO 2 oxide film increases when the oxide thickness gets decreased, having a value between 0.3m e and 0.9m e . Upon assuming constant electron effective mass at 0.5m e in oxide film, Hadjadj et al 22 added the effect of oxide thickness on electron affinity difference for 5, 7, and 12 nm thick oxides for the temperature ranging from 23 to 300°C.…”
Section: ͑8͒mentioning
confidence: 99%
“…16,33,34 It is shown that there is a conflict, if the effective mass is taken as a constant when calculating the barrier height, or if the barrier height is taken as a constant when calculating the effective mass. 15 Some researchers additionally tried to formulize the effective mass, and/or barrier height in terms of nitrogen percentage content in the oxide film.…”
Section: ͑8͒mentioning
confidence: 99%
“…Two electron masses enter this equation: the density-of-states mass in the plane parallel to the interface m 3D = 2m and m * t = 0.19m 0 equals 2.052m 0 , and the electron mass in the dielectric m diel , which is commonly used as fit parameter [3]. However, in the channel of inverted MOS devices, the strong electric field leads to quantum confinement and the assumption of continuum tunneling is no more justified.…”
Section: Tunneling From Continuum Versus Quasi-bound Statesmentioning
confidence: 99%
“…The electron transmittance was then used to calculate leakage current j z by using the standard equation as written in Eq. (3) [11].…”
Section: Theoretical Modelmentioning
confidence: 99%